Pendampingan dan Pembuatan Nomor Induk Berusaha (NIB) Berbasis Teknologi untuk Meningkatkan Efisiensi dan Transparansi dalam Pendaftaran Usaha Bagi UMKM Desa Nglebak (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
In Kabupaten Jombang, Kecamatan Bareng, there has been an increase in the number of business actors. Even though it is important, many of them do not realize how essential it is to have business legality, such as a Business Identification Number (NIB), which greatly influences their business operations. This legality is just one of the many benefits that come with having a NIB under company law. This community service program aims to increase awareness of the ease of making NIB permits using technology for Micro, Small, and Medium Enterprises (MSMEs) in Nglebak Village. Through this service approach, we guide clients on how to use the Online Single Submission (OSS) application to manage NIB online. By using their cell phones, MSME actors are directed to provide the necessary information, such as their identity cards (KTP) and business certificates. The result of this support is an output in the form of a NIB certificate that can be printed by business actors, which is given together with guidance from the speaker. This program is expected to help our partners find solutions to the challenges they face, and it is believed that this kind of community service initiative will make a positive contribution to the development of MSMEs in the area.